2002
DOI: 10.1177/088421702129004796
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Intake of Young Women

Abstract: Inadequate folic acid intake is common in young women ages 18-24. These young women frequently have poor nutritional habits and are usually noncontemplators of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Hilton reported that inadequate folic acid intake was common in young women aged 18 -24 years; the young women frequently had poor nutritional habits and were usually non-contemplators of pregnancy 23 . Amitai et al reported that 17 -19-year-old women had a lower rate of folic acid utilisation than 25 -29-year-old women in the Israeli population 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Hilton reported that inadequate folic acid intake was common in young women aged 18 -24 years; the young women frequently had poor nutritional habits and were usually non-contemplators of pregnancy 23 . Amitai et al reported that 17 -19-year-old women had a lower rate of folic acid utilisation than 25 -29-year-old women in the Israeli population 11 .…”
Section: Discussionmentioning
confidence: 99%
“…(2006) (120) ; Hilton (2002) (121) ; Kloeblen (1999) (122) ; Kloeblen & Batish (1999) (123) ; Lynch (2002) (128) ; Power et al (2000) (129) ; Rosenberg et al…”
Section: Spainmentioning
confidence: 99%
“…Another study, conducted in North Carolina, found that many women ages 18 to 24 years had poor nutritional habits and were noncontemplators of pregnancy (Hilton, 2002). All participants in the study had inadequate intake of folic acid, attributed to the participants' lack of knowledge about folic acid and its prevention of birth defects.…”
mentioning
confidence: 92%